Ocenka techniceskoj podgotovlennosti prygunov trojnym pryžkom v faze prizemlenija - Ogandzhanov, A. L.; Kosikhin, V. P.; Sokunova, S. F.; Moshkin, I. I. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The performance in athletics jumps depends on technical readiness of jumping athletes. The technique of reference-flight phases and run-off is quite well researched by specialists and illuminated in the scientific and methodological literature. But the landing phase is a little-studied phase of horizontal jumps. However, the effectiveness of this phase largely determines the competitive performance in these jump disciplines. A video analysis of the landing phase in the men`s triple jump, performed after processing video footage at all-Russian competitions, made it possible to determine the criteria for the effectiveness of jumpers performing the final phase of the jump. Statistical analysis of kinematic landing parameters made it possibleto develop model characteristics of the landing efficiency indicator in the men`s triple jump. Indicator is based on estimationof angular parameters of athlete`s position at the moment of sand touching with feet. The control of landing efficiency makes it possible to evaluate the technique of performing this phase of the jump by the athlete. There are special exercises presented at the end of the work, that make it possible to increase technical readiness when performing the landing.